Not a single rough hero: semiotics and responsibility in “The Americans” - Gallo, Giusy (E|C, 2020)
In this article we will try to show that, within television series, there is a type of dual rough hero built following a path whose starting point is an individual subject. This is the case of Elizabeth and Philip Jennings, protagonists of the television series “The Americans”, which will be analyzed through the tools offered by the semiotics of A. J. Greimas' fiction, highlighting the theme of responsibility, of which the text is widely disseminated.